Genetic divergence of cowpea genotypes for resistance to black aphid - Silva, Jefté Ferreira da; Bertini, Cândida Hermínia Campos de Magalhães; Bleicher, Ervino; Moraes, João Gutemberg Leite (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the genetic divergence among cowpea genotypes as to resistance to black aphid (Aphis craccivora), and to identify the best combinations between resistant genotypes. The experimental design was a randomized complete blocks with 51 treatments, represented by genotypes, and four replicates. Plants were infested 15 days after sowing, with five female adults. The number of adults and nymphs, at two and four days after infestation, respectively, and the relationship between them were evaluated. Mulamba & Mock’s sum of ranks index, Mahalanobis’ generalized distances, and Tocher’s optimization method were used to assess the genetic distance among genotypes. The largest differences were observed between the genotypes BRS Guariba and Sete Semanas, and between TVu 410 and Sete Semanas, whereas BRS Guariba and TVu 410 were the most similar. The genotypes BRS Guariba, TVu 410, BRS Paraguaçu, TVu 36, Sempre Verde, TVu 408 P2, Setentão, and Epace 10 show resistance to black aphid. Crossings between Setentão and BRS Guariba, TVu 410, BRS Paraguaçu, TVu 36, TVu 408 P2, and between Epace 10 and Sempre Verde, BRS Guariba and TVu 410 are promising for new genetic combinations in breeding programs to improve resistance to black aphid.